Role of polymorphonuclear leukocytes in silica-induced pulmonary fibrosis. - Adamson, I. Y. (1984)
Silicosis is usually attributed to fibroblast stimulation by secretion of damaged alveolar macrophages (AMs), but the role of polymorphonuclear leukocytes (PMNs) and of continuing cell injury in the pathogenesis has not been fully studied. Mice given intratracheal injections of 2 mg of silica received 3H-thymidine 1 hour before death at intervals to 20 weeks. Cellular populations and lysosomal content of lavage fluids were correlated with morphology, DNA synthesis, and collagen content of the lung. The initial response involved rapid PMN and AM recruitment to the alveoli. Some free particles crossed Type 1 epithelial cells, and silica was found in interstitial macrophages. Focal Type 1 cell damage was rapidly repaired by Type 2 cell proliferation. Although PMN numbers dropped after a few days, they never reached control levels and rose again after 8 weeks; the number of AMs fell to control values from 2 to 8 weeks, then increased again. Glucosaminidase and glucuronidase levels in the lavage fluid were much higher than control levels throughout the study. Increased DNA synthesis by interstitial cells occurred from 2 days to 20 weeks; increased collagen synthesis was found from 4 weeks onward. The continuing inflammatory response of the lung to silica suggests may contribute to fibroblastic stimulation.